'True believers' or numerical terrorism at the nuclear power plant - Walter Kraemer; Gerhard Arminger (Center for Economic Studies and ifo Institute (CESifo), 2010)
For decades, there has been a heated debate about whether or not nuclear power plants contribute to childhood cancer in their respective neighbourhoods, with statisticians testifying on both sides. The present paper points to some flaws in the pro-arguments, taking a recent study prepared for the political party 'Bündnis 90 / Grüne' as a specimen. Typical mistakes include an understatement of the size of tests of significance, disregard of important covariates and extreme reliance on very few selected data points.
Keywords: 330; Krebskrankheit; Kernkraftwerk; Statistischer Test; Bias; Statistischer Fehler; Deutschland